Advances in rotary ultrasonic machining system for hard and brittle materials. (December 2019) - Zhou, Huilin; Zhang, Jianfu; Yu, Dingwen; Feng, Pingfa; Wu, Zhijun; Cai, Wanchong
Rotary ultrasonic machining has been widely used for machining of hard and brittle materials due to the advantages of low cutting force, high machining accuracy, and high surface integrity. Focusing on the development of specialized rotary ultrasonic machining systems, this article summarizes the advances in the functional components and key technologies of rotary ultrasonic machining systems for hard and brittle materials, including the ultrasonic generator, power transfer structure, transducer, ultrasonic horn, and cutting tool. Developments on the automatic frequency tracking method, the establishment of an electrical compensation model for power transfer, the energy conversion characteristics of piezoelectric materials and giant magnetostrictive materials, and the design methods for the ultrasonic horn and cutting tool were elaborated. The principle of magnetostrictive energy conversion, output amplitude characteristics of a giant magnetostrictive transducer, and high-power giant magnetostrictive rotary ultrasonic machining systems were also presented. Future research and developments of rotary ultrasonic machining systems regarding the ultrasonic generator, amplitude stability, energy conversion efficiency, vibration mode, and system integration were finally discussed.